PENGEMBANGAN METODE PEMBELAJARAN KETERAMPILAN MENYIMAK BAHASA ARAB BERBASIS KOOPERATIF TIPE JIGSAW - Rahayu, Lusi Sri; Zukhaira, Zukhaira; Amrullah, Nafis Azmi (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
This research is motivated by the attitudes of class X SMA / MA students who are still adjusting to the new learning environment and not many students have studied Arabic so that students experience learning difficulties, especially in learning Arabic listening skills. This causes some students to lack a sense of responsibility for the learning material so that students do not pay attention to the teacher's explanation. Therefore, the development of learning methods for Arabic listening skills based on cooperative jigsaw type for class X SMA / MA students is needed so that students can have a sense of responsibility for their learning and that of others so that the learning objectives will be achieved properly. This study uses a type of qualitative research with a research and development design (Research and Development). The results of this study are as follows. First, teachers and students want the development of a jigsaw-type cooperative method for Arabic listening skills for class X SMA / MA. Second, the prototype of this method contains the background, assumptions, characteristics of the method, KI, KD, and indicators of Arabic listening skills for class X SMA / MA odd semester, learning steps, evaluation, and assessment criteria. Third, the assessment on the feasibility aspect of the presentation got a value of 44.5, the audio feasibility aspect got a value of 12.75, and the aspect of the feasibility of the method got a value of 30.75. The overall value of the aspects of this learning method is 88 in the very feasible category so that it can be used for learning Arabic listening skills for class X SMA / MA.